Breaking the continuity of the Al2O3 oxide scale by additions of Cr in Co-Al-W-based superalloys. (15th August 2021) - Liang, Zhida; Pyczak, Florian; Stark, Andreas; Rao, Ziyuan; Neumeier, Steffen; Göken, Mathias
Highlights: Additions of small amounts of Cr hinder the formation of a continuous Al2 O3 scale in Si-containing Co-Al-W alloys. Cr alloying can increase the diffusion rate of oxygen in oxide layers. The thickness of oxide layers in Cr-containing alloys is higher than that in Cr-free alloys after short oxidation time. Abstract: The paper presents the effect of small amounts of Cr alloying on the oxidation behavior of a Co-9Al-9W-2Si alloy. A small amount of Cr alloying inhibits the formation of a continuous Al2 O3 scale in the oxide layers. The exact mechanism is explained by studying the transient oxidation stages. Cr addition can increase the diffusion rate of oxygen in the oxidation scale. Al is consumed very fast by forming Co(Al, Cr)2 O4 . This impedes the formation of Al2 O3 . As a result, the few formed Al2 O3 particles do not merge to a continuous scale in the oxide layer.